2019
DOI: 10.3390/ijerph16142484
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Oral Health Related Behaviour and Gum Bleeding of Adolescents in Slovakia in Relation to Socioeconomic Status of Their Parents: Cross-Sectional Study Based on Representative Data Collection

Abstract: Background: Oral health strongly affects overall health and is related to many factors. The aim of our study was to analyse oral health related behaviours (OHRBs) and gum bleeding among Slovak adolescents and assess the effect of socioeconomic factors on the outcomes. Methods: Data from the Health Behaviour in School-aged Children study (HBSC) were used (N = 8896, age range = 10–16 years, M = 13.4; SD = 1.4; 50.9% boys). Sociodemographic and socioeconomic indicators and frequency of OHRBs (dental hygiene, toot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…In the Czech Republic, the HBSC indicated that 32–38% of male and 21% of female adolescents were not brushing their teeth twice a day, even though there was an observed positive trend towards the twice-daily brushing habit among males between 1994 and 2014 [ 99 ]. In our sample, the gender-based differences were not statistically significant in HU-DBI scores and the vast majority of items responses, which is in contrast to what was previously reported about oral health behaviours and awareness of general Czech and Slovak populations [ 96 , 97 , 98 , 99 ]. Consequently, one may put forward that dental education can contribute to squeezing or probably closing the gender gaps in oral health attitudes and behaviours, which might be a sound reasoning for population-level interventions that target oral health literacy of the public [ 100 , 101 , 102 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the Czech Republic, the HBSC indicated that 32–38% of male and 21% of female adolescents were not brushing their teeth twice a day, even though there was an observed positive trend towards the twice-daily brushing habit among males between 1994 and 2014 [ 99 ]. In our sample, the gender-based differences were not statistically significant in HU-DBI scores and the vast majority of items responses, which is in contrast to what was previously reported about oral health behaviours and awareness of general Czech and Slovak populations [ 96 , 97 , 98 , 99 ]. Consequently, one may put forward that dental education can contribute to squeezing or probably closing the gender gaps in oral health attitudes and behaviours, which might be a sound reasoning for population-level interventions that target oral health literacy of the public [ 100 , 101 , 102 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, Samohyl et al 2021 concluded that avoidance of preventive oral healthcare was significantly more common among male adolescents than females in Slovakia [ 97 ]. The Health Behaviour in School-aged Children (HBSC) study found a significant difference between female (71.7%) and male (54.8%) adolescents in Slovakia in terms of twice-daily toothbrushing [ 98 ]. In the Czech Republic, the HBSC indicated that 32–38% of male and 21% of female adolescents were not brushing their teeth twice a day, even though there was an observed positive trend towards the twice-daily brushing habit among males between 1994 and 2014 [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides preventive dental check-ups, they checked self-reported dental hygiene, toothbrush changing, and gum bleeding. Attending dental preventive check-ups was associated with female gender, lower age, higher family affluence, higher educational level, and employment of parents [21]. In the study by Aalsma et al [26] analyzing parents' and adolescents' doubts about preventive care, a significant adolescents who discussed health with their parents and visiting the special medical provider on regular basis was found.…”
Section: Discussionmentioning
confidence: 98%
“…The most frequent motivation for visiting a dental office was to receive conservative treatment, while the least common reasons were prophylaxis and tooth injuries [20]. The study on the large and nationally representative sample based on internationally elaborated study protocol of the Health Behaviour in School-aged Children study (HBSC) has been recently published in Slovakia [21]. The study provided representative findings on oral health related behaviours (OHRBs) in Slovakia and has shown important associations of socioeconomic factors related to adolescents' oral health issues in the age range of 10-16 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation